Healthy Smart Baking Recipes Mobile Application - Tan, Yi Tiang (2023)
Baking is a great way for people to express their creativity. It isn't just about thinking in the moment and following details, it's also about thinking about the recipe, the dish, how you intend to use it, with whom you intend to share it, and at what time. Hence, it is a great way to maintain this balance between the moment and the bigger picture. However, a hectic lifestyle makes it difficult for most people to study baking and appreciate its process. In this paper, we will focus on developing a baking recipes mobile application that is mainly for the user who has no experiences in baking to learn simple recipes. The aim of this project is to study the difficulties and limitation faced by people with suffer health problems and non-experienced users when learning new baking recipes and to develop a mobile application which digitalized baking recipes and bring convenience to users. The scope of this project is to provide recipe details, ingredient list, nutritional facts and communication function.